Pematahan Dormansi dan Viabilitas Benih Aren (Arenga pinnata Merr) Pada Berbagai Media Tanam dan Perlakuan Fisik - Nur Hafizah (ZIRAA'AH MAJALAH ILMIAH PERTANIAN, 2013)
Intention of this research is to know the interaction influence of some media plant and physical treatment, knowing best combination of media plant and physical treatment and know the media plant and best physical treatment to fracturing of dormansi and viabilitas of sugar palm seed.   This research  was concuted on the experimental land at Jumba Amuntai of South arch, during 4 month, device utilized in this research is Random Device of Group ( RAK), with the factorial attempt pattern two factor that is : (I) Media plant the (T) with four level : t0 = sand + land;ground  (1 : 1); t1 = sand + fertilize the cage of chicken dirt (1 : 1); t2 = sand + chaff (1:1) and t3 = sand + sawdust (1:1). (II) Treatment of seed physical (F) with four level : f0 = without physical treatment; fl = cut the parallelogram of near by bydm soriyt eye ± 5 mm; f2 = sharpened circular precisely bydm soriyt eye; f3 = rubbed by a precise emery paper of bydm soriyt eye.    Result of research indicate that the media interaction plant and physical treatment have an effect on the reality to germination percentage, fast of germination, sum up the leaf, long of upper seed and dry weight of sprout. Combination of media plant and best physical treatment at germination percentage that is t2f1 is 53,25 %, accelerateing germination at t0f2 is 6,65 day, sum up the leaf that is t1f3 is 1,87 piece of, upper seed length that is t1f2 is 35,67 dry cm weight and of sprout at tlf0 is 1,86 g. Single factor of media plant best there are at media plant the sand + fertilize the cage and very influencing to growth perception that is length of bydm soriyt dry weight and of sprout. Single factor of best physical treatment is cuting the near by eye of bydm soriyt and sharpened circular precisely